The Transcendence Dimensions of Prophetic Leadership - Atiqullah,; Zainol Hasan,; Ali Nurhadi,; Kacung Wahyudi, (TADRIS: Jurnal Pendidikan Islam, 2023)
This study examines the traces of Kiai Abdul Wahid Khudzaifah's life and his role as a pioneer and public figure as well as his transcendence dimension prophetically influence character development as spirit and personality of the Santri (students). This study uses a descriptive approach with data collection techniques of interviews, participant Kiai, Leadership; Transcendence; Character Development; Santri observation, and documentation. This research aims to, firstly, describe the life of Kiai Abdul Wahid Khudzaifah when he was in the Islamic boarding school; secondly, to describe the role of Kiai Abdul Wahid Khudzaifah as a pioneer in establishing educational institutions, as a great figure in mass organizations and his wisdom as Murshid Thoriqah Naqsyabandiyah Ahmadiyah Mudzhariyah; and the last, to describe the prophetic transcendence dimension of Kiai Abdul Wahid Khudzaifah's leadership in influencing character development as spirit and personality of the students in managing Islamic Education. The results showed that, firstly, Kiai Abdul Wahid Khudzaifah was a scholar who produced works related to religion, Sufism, and language. Second, Kiai Abdul Wahid Khudzaifah plays and works his role well as a public figure for Islamic Education, the figure of Religious Organization namely Nahdhatul Ulama (NU), as well as Sufi and Murshid figure of Thoriqah Naqsabandiyah Ahmadiyah Mudzhariyah. Third, the behavior and leadership of Kiai Abdul Wahid Khudzaifah, in prophetic transcendent, influence the character development of the students in the form of trustful, patience, sincerity, istiqamah, simplicity and humility, and firmness in his action.